Penguatan Kerjasama Bumdes, Pelaku Usaha Wisata, Dan Pokdarwis Dalam Optimalisasi Cenderamata Khas Desa Wisata Gili Gede Indah - Ika Wijayanti (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Gili Gede Indah Tourism Village is one of the leading tourist destinations on the southwest coast of Lombok Island. The visiting tourists are predominantly foreign. Although Gili Gede Tourism Village has the potential of its resources as a tourist attraction, it is not yet supported by the supporting aspect of tourism, namely souvenirs. This village has not yet developed souvenirs as a distinctive souvenir, although there are crafts made from marine waste, they are not yet optimal in terms of marketing, packaging, and product innovation. The lack of innovation, skills, and networks is the reason for the suboptimal presence of typical souvenirs. The purpose of this service is to provide support to Bumdes, tourism business actors, and pokdarwis as the main drivers for optimizing the unique souvenirs of Gili Gede Indah Tourism Village. The activity will begin with an FGD (Focus Group Discussion) to identify existing problems at the service location, followed by socialization and strengthening cooperation in optimizing souvenirs, particularly in product marketing.